The Comradery Between An FBI Agent And A Forger As Seen In Frank Abagnale’s Catch Me If You Can - Aslamudini, Aslamudini; Raflis, Raflis (Jurnal Ilmiah Pendidikan Scholastic, 2025)
The title of this research is “The Comradery Between an FBI Agent and a Forger as seen in Frank Abagnale's Catch Me If You Can”. This research problem focuses on the character differences between O’Riley as an FBI agent and Frank as a forger and the development of interpersonal relationships that occur between them as reflected in the novel Catch Me If You Can.The method used in this research is descriptive qualitative research method and the approach used is literary psychology with Freud's psychological theory (1955) and Peplau's interpersonal relationship theory (1952). The data in this novel is presented in the form of quotations and sentences derived from the characters of O'Riley and Frank, which explain their respective personalities and the development of their interpersonal relationships. The data collection technique used in this research is based on reading, marking, recording and categorising the data. This was done with the aim of distinguishing between data related to the personalities of O'Riley and Frank and data related to the interaction between the two characters, as well as its impact on the development of interpersonal relationships in Abagnale's Catch Me If You Can.The results of this research show that Frank's personality in Abagnale's Catch Me If You Can is dominated by the Id, with less influence from the Ego and Superego. This is due to his parents' divorce and his disadvantaged childhood, which drove him to seek pleasure through delinquency and crime, while O'Riley's personality is characterised by the dominance of the Superego over the Id and Ego, due to his role as an FBI agent, who has the responsibility to uphold justice. In the interactions that make up the development of the interpersonal relationship between them, this is due to the emergence of mutual respect and appreciation in their interactions over time.